Pengaruh Media Dan Interval Pemberian Air Bioflok Terhadap Pertumbuhan Dan Hasil Tanaman Padi Varietas Ir 64 Dan Mentik Wangi Dengan Sistem Tanam Dalam Polybag - Evane Dwi Idolianto; Yacobus Sunaryo; Darnawi (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to determine the effect of biofloc watering media and intervals on the growth and yield of rice varieties IR 64 and fragrant mentik using a polybag planting system. The research was conducted in January - May 2022 at the Greenhouse located in Gang Kanthil, RW.05, Rejowinangun Village, Kotagede District, Yogyakarta City, Yogyakarta Special Region. The research area is located at an altitude of 113 meters above sea level, an average temperature of 28oC and an average of 2000-3000 mm of rain per year. The study was a 2 x 2 x 2 factorial experiment. The first factor was variety, namely IR 64 (V1) and fragrant mentik (V2). The second factor is the planting medium, namely soil planting media (M1) and soil + manure growing media (M2). The third factor is the biofloc watering interval, that is, the biofloc watering interval is 2 days 1x (B1) and the biofloc watering interval is 4 days 1x (B2). Parameters observed were plant height, number of stems, weight of dry stover, number of panicles, length of panicles, number of grain per hill, grain weight per hill, weight of 200 grain, and percentage of filled grain. The results showed that there was no interaction between varieties, growing media, and biofloc watering intervals on the growth and yield variables of rice plants. The results showed that there was an interaction between the planting medium and the biofloc watering interval on the number of stems. Soil + manure (M2) growing media produced a higher dry stover weight than soil growing media (M1). The fragrant mentik variety (V2) produced higher grain weight per clump than the IR 64 variety (V1). In the growth variable, the biofloc watering interval 2 days 1x (B1) produced a higher number of stems compared to the biofloc watering interval 4 days 1 x (B2), while the yield variable the biofloc watering interval gave the same grain weight per clump.